The Development of Interactive Learning Media for Islamic Religious Education in Elementary Schools in Indonesia - Happy Susanto; Siti Marpuah; Sudarmadi; Devid Dwi Erwahyudin; Nani Wahyuni (Scientia Publica Media, 2024)
In today’s digital era, conventional teaching methods often fail to captivate students, making interactive media a promising solution. Interactive media combines visual, audio, and participatory elements, providing a more engaging and effective learning experience. The development process includes analyzing student needs and curriculum, selecting appropriate technology, creating interactive content, conducting trials, and evaluating effectiveness. This study uses a qualitative approach. Primary data sources in qualitative research are the words of the interview results obtained from primary data including respondents from teachers and students in SDMT Ponorogo. Data collection is carried out by means of snowball sampling. The data collection technique in this study is through observation, in-depth interviews and documentation. The data obtained during the study, both primary and secondary data are then processed and analyzed using Miles and Huberman model. The validity test of data in qualitative research includes tests, credibility, transferability, dependability, and confirmability. The article highlights the benefits of interactive media, including increased student motivation, improved understanding of abstract religious concepts, and the development of critical thinking skills. This approach not only modernizes religious education but also ensures that students remain interested and actively involved in learning. Through proper testing and implementation, interactive media can significantly enhance the quality of Islamic Religious Education at SDMT Ponorogo. The developed media, which consists of animated videos, interactive quizzes, and educational games, is able to make the learning process more engaging and increase student engagement.